2022
DOI: 10.1007/s11914-022-00736-9
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Deficits and Cognitive Impairment: Epidemiological Evidence and Biological Mechanisms

Abstract: Purpose of Review Cognitive impairment is associated with obesity, sarcopenia, and osteoporosis. However, no critical appraisal of the literature on the relationship between musculoskeletal deficits and cognitive impairment, focusing on the epidemiological evidence and biological mechanisms, has been published to date. Herein, we critically evaluate the literature published over the past 3 years, emphasizing interesting and important new findings, and provide an outline of future directions that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 117 publications
(133 reference statements)
0
9
1
Order By: Relevance
“…Besides, it was worthwhile to consider the other limitations in our study, such as sample size, the method to measure sarcopenia, and the selected cutoff values for ADL disability. On the contrary, previous reports as well as ours showed a closer bidirectional relationship between musculoskeletal health and cognitive function [40], although the exact causal relationship remained to be elucidated. In our study, the possible osteosarcopenia group showed poorer GDS-5 scores, although there was no significant difference in depressive mood.…”
Section: Discussioncontrasting
confidence: 84%
“…Besides, it was worthwhile to consider the other limitations in our study, such as sample size, the method to measure sarcopenia, and the selected cutoff values for ADL disability. On the contrary, previous reports as well as ours showed a closer bidirectional relationship between musculoskeletal health and cognitive function [40], although the exact causal relationship remained to be elucidated. In our study, the possible osteosarcopenia group showed poorer GDS-5 scores, although there was no significant difference in depressive mood.…”
Section: Discussioncontrasting
confidence: 84%
“…Four reviews examined the link between musculoskeletal processes and cognitive function. Sui et al (2022) reviewed research linking musculoskeletal activity/inactivity and cognition, suggesting an important role for factors (BDNF, myokines and osteokines) released during physical activity in prevention of cognitive decline. In contrast, muscle loss, weakness and frailty are associated with increased inflammation and impaired neuroplasticity in the brain, leading to CI.…”
Section: Resultsmentioning
confidence: 99%
“…6 Masticatory muscle loss and weakness are associated with systemic and central inflammation, leading to impaired synaptic neuroplasticity and cognitive impairment. 7 Neurotrophins are responsible for the development, maintenance, and regeneration of both the central and peripheral nervous systems in the synapses of the brain, and some of them are released during skeletal muscle contraction. 8 Furthermore, mastication activates various cortical regions of the brain, and increased cerebral blood oxygenation levels in the hippocampus and prefrontal cortex aid learning and memory processes.…”
Section: Association Of Temporomandibular Disorders and Reduced Masti...mentioning
confidence: 99%